Join the Holy Spirit on Zoom: African Pentecostal churches and their liturgical practices during COVID-19 - Addo, Giuseppina (Approaching religion, 2021)
The COVID-19 global pandemic impacted all social relations, including the way religious communities engage in worship services. Due to strict social distancing protocols, the only viable solution for many congregations was online worship. This article investigates how platforms in cyberspace, such as Zoom, can provide a substitute for the core religious practices found in physical worship services, particularly for African Pentecostal believers who rely heavily on the aesthetic and sensory experience of their religious environment. Drawing on the theoretical concept of affordance, it is argued that digital affordances such as the chat box and emojis are used by believers to communicate affective moments arising from the sensory experience of worship. Members of the congregation become ‘digital spiritual hype people’ who render support to leaders in order to create and regenerate an affective environment where the presence of the Holy Spirit can be felt. The Holy Spirit, a fundamental pillar for Evangelical Christians, is understood as an embedded presence within the digital infrastructure. The internet connection, the phone and computers and screens are all re-appropriated as spiritual tools through which miraculous healing can be dispensed to believers in need. This research stands at a critical juncture between what might be termed the ‘pre-COVID era’ and the ‘post-COVID era’. As vaccination plans continue to roll out and social distancing measures are slowly being lifted, a ‘post-COVID era’ for African Pentecostals means negotiating the boundaries between online and offline spaces to fulfil core religious practices.